Where Schön and Simon agree: The rationality of design. (March 2022) - Schaathun, Hans Georg
Abstract : Simon and Schön are commonly seen to represent two conflicting views on design method, but this interpretation has been challenged in recent years. In this paper we discuss their differences and agreements in more depth. Both of them agree on a rationality which is distinct from science and its reliance on universal truth. They depend on a practical reason, and what Aristotle calls the calculative part of the soul, which deals with the contingencies of real world problems, and still let us know, and share, truth. One discrepancy remains between Simon and Schön. Simon does not tell us how we identify the changing goals of man. Schön addresses this by invoking the distinctly human power to see-as . Highlights: There is no conflict between intuition and rationality in design processes. As much as intuition, Schön emphasises rational evaluation and testing in design. Intuition is information processing and has an important role in Simon's models. Aristotle's logistikon concerns the particular truths that we search in design.